Intermediate algebra - Lial, Margaret L.; Miller, Charles D. (Glenview, Illinois : HarperCollins Publishers, 1988)
It continues to address the needs of both the student and the instructor. Clear explanations keyed to objectives, numerous examples detailing the structures of each problem, carefully graded exercises.
1. The real numbers -- 2. Linear equations and inequalities -- 3. Exponents and polynomial -- 4. Rational expressions -- 5. Rational exponents and radicals -- 6. Quadratic equations and inequalities -- 7. The straight line -- 8 .Systems of linear equations -- 9. Conic sections -- 10. Functions -- 11. Exponential and logarithmic functions -- 12. Sequences and series.
Includes index.
Keywords: ALGEBRA